Evaluation of Structural Features and Hydrocarbon Reservoir Potential of the Baturaja Formation Using Seismic Envelope and Sweetness Attributes - Alifa Tri Handayani; Aryono Adhi, Mochamad; Eka Nurcahya, Budi (Universitas Negeri Semarang, 2023)
The Afara Field is located around the South Sumatra Basin, which is estimated to contain oil and gas hydrocarbon deposits. The method that can be used for hydrocarbon reserve exploration is the seismic method. Interpretation analysis is carried out by analyzing seismic attributes to determine the amplitude value, shape, and position of seismic waves to identify depositional environments, fluvial or channels, carbonate buildups, to detect fractures and faults, and to provide a direct hydrocarbon indicator (DHI). In this study, the seismic attributes used are the envelope and sweetness attributes to identify the presence of reservoirs, and the ant-tracking attribute is used to identify fault structures around the study area. The results obtained from the analysis carried out on the envelope attribute are the presence of hydrocarbon deposit areas seen from the bright-spot which indicates that the resulting amplitude value is high. The amplitude value has a range of values ​​around 280,000 ms to 440,000 ms located around the UPI-40 and UPI-60 wells. This is validated by the sweetness attribute, which is characterized by the presence of a sweet spot with a value ranging from 60,000 ms to 80,000 ms. The results of the geometric attribute analysis revealed the presence of faults in the study area.